ANALISIS KEMAMPUAN BERFIKIR KRITIS MATEMATIK SERTA KEMANDIRIAAN BELAJAR SISWA SMP TERHADAP MATERI SPLDV - Fauziah Hidayat; Padillah Akbar; Martin Bernard (Departement of Mathematics Education, 2019)
Students' negative suggestions for mathematics make mathematics not so much liked and desired by students. Critical thinking ability is very important to have, because it can help us in thinking rationally in overcoming the problems we face. This study aims to analyze the independence of learning and critical thinking mathematically students at Al-Mukhtariyah Mande Mts. This study used descriptive qualitative method. Researchers act as observers, provide test questions and provide questionnaires to students. The instruments used are a description test and a learning independence scale. The study was conducted on class VIII students, namely in class VIII-B and VIII-D at the Al-Mukhtariyah Mande Mts. In class VIII-B, there were 25 students, 13 students were male and 12 were female students. In class VIII-D, there were 33 students, 15 students were male and 18 were female students. Researchers use indicators of critical thinking: interpretation, analysis, evaluation, drawing conclusions, explanations, independence. Based on the results of the description test, it was concluded that (1) students 'overall mathematical critical thinking ability was in the low category, (2) students' responses in solving critical thinking problems were still very low, (3) overall student learning independence was at a moderate level and students are not accustomed to using indicators of independence of learning correctly. (4) there is a close relationship between learning independence and students' critical thinking skills